ANALISIS PENGELOLAAN DANA ABADI TELKOM UNIVERSITY - Riswan, Dedy; Hastuti, Tri Yuni; Munadi, Muhammad; Supriyanto, Supriyanto (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
This study aims to analyze transparency and accountability in the management of the Endowment Fund at Telkom University based on quarterly and annual reports. The Endowment Fund acts as a strategic source of funding to support various programs, ranging from scholarships, research, community service, facility development, to social and religious activities. This study uses a quantitative and qualitative descriptive approach through analysis of official report documents, interviews, and activity observations. The results of the study show that from 2017 to 2024, Telkom University has succeeded in collecting more than IDR 37 billion, with significant growth especially in the last three years. Diversification of funding sources, alumni involvement, and investment through sharia instruments are the advantages of this endowment fund management. Although the management is considered quite transparent and accountable, there are still some shortcomings in the inclusion of budget details in certain activity reports. These findings are expected to be a reference for other higher education institutions in designing a sustainable, inclusive, and welfare-oriented endowment fund management system. ABSTRAKPenelitian ini bertujuan untuk menganalisis transparansi dan akuntabilitas dalam pengelolaan Dana Abadi di Telkom University berdasarkan laporan triwulan dan tahunan. Dana Abadi berperan sebagai sumber pembiayaan strategis untuk mendukung beragam program, mulai dari beasiswa, riset, pengabdian masyarakat, pengembangan fasilitas, hingga kegiatan sosial dan keagamaan. Studi ini menggunakan pendekatan deskriptif kuantitatif dan kualitatif melalui analisis dokumen laporan resmi, wawancara, dan observasi kegiatan. Hasil penelitian menunjukkan bahwa sejak 2017 hingga 2024, Telkom University telah berhasil menghimpun lebih dari Rp37 miliar, dengan pertumbuhan signifikan terutama dalam tiga tahun terakhir. Diversifikasi sumber dana, keterlibatan alumni, serta investasi melalui instrumen syariah menjadi keunggulan pengelolaan dana abadi ini. Meskipun pengelolaan dinilai cukup transparan dan akuntabel, masih terdapat beberapa kekurangan dalam pencantuman rincian anggaran pada laporan kegiatan tertentu. Temuan ini diharapkan dapat menjadi acuan bagi institusi pendidikan tinggi lainnya dalam merancang sistem pengelolaan dana abadi yang berkelanjutan, inklusif, dan berorientasi pada kemaslahatan.